IMPROVING STUDENTS WRITING SKILL BY USING PICTURE AT THE TWELFTH YEAR STUDENTS OF SMA PESANTREN MODERN DATOK SULAIMAN PUTRA PALOPO - Masruddin Masruddin; Kurnia Kurnia (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2015)
The objective of this study to find out the effectiveness of using picture in improving students writing skill at the twelfth year of SMA Pesantren Modern Datok Sulaiman Putra Palopo. The result of this research is expected: 1) for teacher: the media will be more helpful for all teacher in teaching and learning process for improving students writing skill. 2) for students: by using picture, the students will be easy to write and improve their writing skill. 3) for the next researcher as reference. This study applied Quasi-experimental method. The population of this research was the students of the twelfth year of SMA Pesantren Modern Datok Sulaiman Palopo. The sample was taken by using purposive sampling. The number of sample was 10 students of XII IPA and 10 students of XII IPS. The result of this research shows it is effective to use picture in teaching writing. The result of the data analysis shows that by using picture can improve the students writing skills.